Is economic development affected by the leaders' education levels? Evidence from India - Chandan Jain; Shagun Kashyap; Rahul Lahoti; Soham Sahoo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Although formal education is often considered an indicator of political leaders' quality, the evidence on the effectiveness of educated leaders is mixed. Besides, minimum education qualifications are increasingly being used as requirements for contesting elections, making it critical to understand the role of politicians' education in their performance. We investigate the impact of electing an educated politician on economic development in the politician's constituency in India. We use constituency-level panel data on the intensity of night-time lights to measure economic activity. Our identification strategy is based on a regression discontinuity design that exploits quasirandom outcomes of close elections between educated and less-educated politicians. We find that narrowly electing a graduate leader, as compared to a non-graduate leader, in the state assembly constituency increases the growth rate of night-time lights by about three percentage points in the constituency. As pathways, we find that graduate leaders improve the provision of roads, electricity, and power; however, they do not significantly impact the overall provision of public goods. In comparison with findings from other studies in the literature, our result suggests that the impact of formal education of the leader is weaker than the leader's other characteristics, such as gender or criminality.
Keywords: D72; H11; H41; O40; 330; educated political leaders; night-time lights; close elections; public goods; India